Financial Ratio Analysis at PT. Adaro Energy Tbk. Based on The 2017 – 2020 Financial Statements - Limbong, Christine Herawati; Simanjorang, Elida Florentina Sinaga; Harahap, Nova Jayanti; Nasution, Zulkarnain (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2021)
Every company must have financial reports that record capital, profits, losses, production wages, salary payments, which are related to the whole business. This report is called a financial report or financial report which records all information about a company's finances. The financial report is the final result of the process of recording financial transaction activities in a company that describes the company's financial condition in an accounting period and is a general description of the performance of a company. Where the purpose of making financial statements is to communicate the economic resources (assets), and obligations of an entity at a certain time, and the capital owned by the company. One way to get good financial reports is to compare the numbers in the financial statements. In making comparisons known as financial ratio analysis. The financial ratios used are profitability ratios and liquidity ratios. The results of these financial ratios will show the health condition of the company in question and are used to assess management's performance in a period whether it has achieved the targets as set and assesses management's ability to effectively empower company resources.